Analisis Faktor Penyebab Ide Bunuh Diri pada Remaja: Literatur Review - Ipung Jatmiko; Rizki Fitryasari; Rr Dian Tristiana (Jurnal Ilmu Keperawatan Jiwa, 2021)
Suicide is cause of death in 15 -29 years age group number second  in 2014. This study aims to explain related to internal and eksternal factors and suicide idea among adolescent. Study literature review was used in this study with sample adolescent age 10 – 19 years conducted three electronic databases (Scopus, Science Direct and ProQuest) which published between January 2015 - September 2020. Analysis of selected journals used prisma check list by assessing a suitable journal. with the aim of review literature topics ranging from title, abstract, background, research methods, research results.  Journal quality was assessed by 3 researchers using critical appraisal checklist from The Joanna Briggs Institute and process selection a literature using The Center for Review and Dissemination. Internal factors cause suicidal ideation are biological, demographics, psychological, deviant behavior, and lifestyle. External factors cause suicidal ideation are negative life experiences, family, economic, friendship, technology and education. We found that peer support, good relationships with classmates and teachers, physical activity, a good diet and positive religious coping were protective factors against suicidal ideation. Internal factors such as history of previous suicide, depression, anxiety and external factors such as adequate food intake, history of suicide in family are variables that have highest potential to cause suicidal ideation.